Effect of ACACIA Melanoxylon in Agroforestry System on Biomass Production and Erosion Control In High Hills of Nilgiris - madhu, M.; Tripathi, K.P.; Raghupathy, R.; Seshachalam, N.; Samraj, P. (Journal of Soil and Water Conservation, 2022)
The field experiment was conducted at research farm of Central Soil and Water Conservation Research and Training Institute, Research centre, Udhagamandalam (T.N.) from 1988 to 1996. The fodder acacia tree can be grown successfully in agro forestry system without tree crop interface/competition for the resources. The highest biomass production (Vegetable crops, grass, tree biomass and yield of tea leaves) with lesser runoff and soil loss was observed from the row spacing of Acacia melanoxylon at 6.0 m horizontal interval (VI: 1.2 m) with conservation measures at 19 per cent slope. Potato-Cabbage sequence year after year increased the infestation of club root disease of cabbage.